BIKE SHARING; Pelaksanaan Program Jogja Bike Sebagai Transportasi Lokal untuk Wisatawan Yogyakarta: Array - Pahmi Amri; Dita Fisdia Adni; Artha Yudilla (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
A Yogyakarta City Government program as a form of public service to the public and tourists in the city of Yogyakarta. The program is called Jogja Ada Bicycles or better known as Jogja Bike. The concept of this program is Sharing Bike which can be accessed by the general public through applications made by application development companies and in collaboration with the Yogyakarta City Government to restore the previous city branding of Yogyakarta as a City of Bicycles, besides this program also plays a role in stimulating the general public to use bicycles. in all daily activities. This study aims to determine the extent to which the implementation of the Jogja Bike Program in improving tourism sector services can be carried out by the Yogyakarta city government. This paper uses a qualitative analysis method by applying the SNA Social Network Analysis approach. The SNA approach is implemented by using NVIVO Tools to help process coding data obtained from reputable local websites as a source of research information data. The results of the discussion show that the implementation of the jogja bike program in the city of Yogkarta has succeeded in realizing the tourism sector services by providing bicycles as an alternative transportation for tourists to access a number of tourist objects in the city of Yogyakarta.